A Comparison of the Sociolinguistic Situation of Pupils Attending Polish Schools in Mostyska, Horodok (Ukraine) and Šalčininkai (Lithuania) - Geben, Kinga; Zielińska, Maria (Slavistica Vilnensis, 2017)
The aim of the article is to analyze the sociolinguistic situation of pupils attending Polish schools in Mostyska, Horodok (Ukraine) and Šalčininkai (Lithuania). The comparison of sociolinguistic data of youth receiving education in the Polish language in Lithuania and Ukraine was based on questionnaire material collected by authors in May 2015. 40 questionnaires have been filled out by pupils of the 7th and 8th grades (14–15 years old) in each town, Šalčininkai and Horodok; in Mostyska, 62 pupils of the 9th–11th grades (15–17 years old) have filled out the questionnaires. The research hypothesis is the following: The sociolinguistic situation of youth attending Polish schools in different countries and participating in various language contacts is similar. The analysis includes declarations of nationality and descent, mother tongue, prestige language and situational usage as well as the knowledge of particular languages.
Keywords: Polish schools; Lithuania; Ukraine; prestige language; language awareness